Non-neuropathic Niemann-Pick disease with sea blue histolocytic involment of the lungs: A case report - Buket ALTUNTAŞ,; Neşe YARALI,; Semanur KUYUCU,; Zafer ARSLAN,; Ülker ERTAN,; Nilüfer ARDA,; Ayşegül AKÇAYOZ,; Tahsin TEZİÇ, (Turkish Journal of Gastroenterology, 2019)
-